Enfermedades causadas por virus - Morales, Francisco José (United Nations Development Programme, 1985)
The symptomatology and control measures of BCMV, BYMV, BGMV, and bean chlorotic mottle virus are briefly described. General aspects regarding the genetic control of viruses and the use of chemicals to control insect vectors are discussed. Some bean lines and/or var. resistant to BCMV, BGMV, and bean chlorotic mottle virus are mentioned. (CIAT)